Correction: Housefly (Musca domestica) larvae powder, preventing oxidative stress injury via regulation of UCP4 and CyclinD1 and modulation of JNK and P38 signaling in APP/PS1 mice. Issue 10 (24th September 2019) - He, Yinru; Yang, Xia; Jiao, Mengya; Anoopkumar-Dukie, Shailendra; Zeng, Yu; Mei, Hanfang
Abstract : Correction for 'Housefly ( Musca domestica ) larvae powder, preventing oxidative stress injury via regulation of UCP4 and CyclinD1 and modulation of JNK and P38 signaling in APP/PS1 mice' by Yinru He et al., Food Funct., 2019, 10, 235–243.